Comparison of outcomes after aortic valve replacement with a mechanical valve or a bioprosthesis using microsimulation - Puvimanasinghe, J P A (Copyright 2004 by Heart, 2004)
Background: Mechanical valves and bioprostheses are widely used for aortic valve replacement. Though previous randomised studies indicate that there is no important difference in outcome after implantation with either type of valve, knowledge of outcomes after aortic valve replacement is incomplete. Objective: To predict age and sex specific outcomes of patients after aortic valve replacement with bileaflet mechanical valves and stented porcine bioprostheses, and to provide evidence based support for the choice of prosthesis. Methods: Meta-analysis of published results of primary aortic valve replacement with bileaflet mechanical prostheses (nine reports, 4274 patients, and 25 726 patient-years) and stented porcine bioprostheses (13 reports, 9007 patients, and 54 151 patient-years) was used to estimate the annual risks of postoperative valve related events and their outcomes. These estimates were entered into a microsimulation model, which was employed to calculate age and sex specific outcomes after aortic valve replacement. Results: Life expectancy (LE) and event-free life expectancy (EFLE) for a 65 year old man after implantation with a mechanical valve or a bioprosthesis were 10.4 and 10.7 years and 7.7 and 8.4 years, respectively. The lifetime risk of at least one valve related event for a mechanical valve was 48%, and for a bioprosthesis, 44%. For LE and EFLE, the age crossover point between the two valve types was 59 and 60 years, respectively. Conclusions: Meta-analysis based microsimulation provides insight into the long term outcome after aortic valve replacement and suggests that the currently recommended age threshold for implanting a bioprosthesis could be lowered further.